Jak z gęsia woda. Northern Kresy (Borderlands) Phrasematic Comparisons in a Formalized Description - Mędelska, Jolanta; Marszałek, Marek (Slavia Orientalis, 2020)
The authors have collected an extensive file of peculiar multi-word units used by Poles living in the North‑eastern Kresy (Borderlands) region. An attempt is made to describe them in a formalized way, as presented by A. Bogusławski in his dictionary probes. The excerpt, however, is heterogeneous, excessively diverse in its formal, generic, functional and semantic terms, and requires the resolution of certain issues that concern not all the phrases, but those of particular generic groups. One such group is the comparative constructions lexicalized as X like Y. The article discusses the problem of the phrasematic status of comparisons, their characteristics in comparison with other groups of phrases and the difficulties faced by the researcher of Northern Kresy (Borderlands) comparative constructions. There is also a draft of several key word articles containing peculiar comparisons, e.g. ktoś kręci się jak wiewiórka w kole, ktoś pisze jak kura grzebie, coś potrzebne komuś jak kogutowi medalion, coś jest słabe jak wilcze oko.
Keywords: phrasematics; phrasematic comparisons; Northern Kresy (Borderlands) Polish